The Role of Parents in the Online Learning Process for Sixth Grade Students at SDN Sari 1 Demak during the Pandemic - Sidiq Wahyu Kuncoro; Mohammad Kanzunnudin; Santoso Santoso (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
This study aims to determine the role of parents in the online learning process for sixth graders at SD N Sari 1 Demak during the pandemic. This research used qualitative research with descriptive method. This research was conducted at SD N Sari 1 Desa Sari Demak. The subjects in this study consisted of parents and sixth graders, totaling eight people. Data collection techniques and instruments employed in this study were observation, interviews, and documentation. The data analysis utilized in this research was data reduction, data presentation, and conclusion drawing. The results revealed that the role of parents in online learning at SD N Sari 1 Demak included parents carrying out two roles at once. The first was being a parent, and the second was as a teacher at home, including providing facilities and infrastructure, encouraging enthusiasm, giving motivation, and directing children according to each child’s talents and interests. However, parents' difficulties in online learning at SD N Sari 1 Demak encompassed parents' educational background, parents' economic level, and difficulties in dividing time between children and work, which also affected parents in guiding children when studying at home.